Optimum design of steel space frames using tabu search and genetic algorithm - De?ertekin, S. Ozgür; Ülker, Mehmet; Hayalio?lu, M. Sedat (My University, 2006)
In this study, an algorithm and its computer program were developed for the optimum design of steel space frames using tabu search method. Two algorithms were used for tabu search and the results obtained from these algorithms were compared. An optimum design algorithm was also developed using genetic algorithm so as to compare the results with the ones obtained from tabu search and to discover the effectiveness of the method. Geometrical nonlinearity was considered and the material was assumed to be linear-elastic in the analysis of the space frames. The lateral and vertical loads, lateral displacement, interstory drift and stress constraints imposed on the frames were taken from the relevant design codes. Moreover, section size constraints was considered in the optimum design. In this study, obtaining of the minimum-weight frames was aimed under the above mentioned loads and constraints. Optimum designs of two steel space frame were performed to show the applications of the developed algorithms and computer programs. More economical designs were obtained from tabu search when compared to genetic algorithms.
Uzay çelik çerçevelerin tabu arama ve genetik algoritma yöntemleriyle optimum tasarimi
Keywords: Computer aided design; Constraint theory; Genetic algorithms; Optimization; Search engines; Structural frames; Geometrical nonlinearity; Optimum design; Space frames; Tabu search; Steel